Análisis de la educación contínua y postgrados de telecomunicaciones en el Ecuador - Ordóñez Vivanco, Cecilia Isabel (2009)
Telecommunications are the primary basis for a country´s development; Ecuador can not be exempt to this reality. The quality of education that is received by habitants of any country is concerned to its own development, for this reason, this document´s objective is to analyze levels of education in function of importance given to telecommunications engineering and masteries related to the mentioned career. This document is mainly interested on academic formation that is offered by institutions to their professionals, evaluating if this instruction is focused on satisfying all kind of demands that are implicit in telecommunications; therefore, we were forced to investigate about technologies and tendencies used by leader enterprises in this market. Starting from these results, suggestions are made in order to improve academic levels and this will allow telecommunications engineers and masteries accelerate improvements and make possible international competitiveness at the same time. A basic table of contents is exposed for the career engineering on telecommunications. This table of content includes three specializations that cover all kind of markets needs and student expectancies. Key subjects are also exposed for any mastery related with telecommunications in order to form professionals from local reality with global development to contribute the modernization of the country and create a much better future.